Mining Corporate Responsibility for Environmental Recovery - Kapugu, Betsy Anggreni; Irwansyah; Wahid, A. M. Yunus; Maskun (International Journal of Psychosocial Rehabilitation, 2020)
The role and control of natural resource management lies in the State as the head of the organization of State power. Looking at the potential wealth of natural resources possessed, the quality of human resources has become one of the important and decisive actors in the natural resource management. This research is a normative-legal research using a statute, case, historical, comparative and conceptual approaches. The results show that There is no other choice for the natural resources management by the government both central or regional besides the implementation of the concept of sustainable development. Environmental priorities are prioritized as priorities that must be prioritized if want to conduct development itself. Certainly, the implementation of the concept of sustainable development leads to the realization of a balance between prosperity and environment are good and sustainable. As a result, both policies, plans and/or programs must be spirited by the obligation to preserve environmental functions and realize sustainable development goals.